The key to Chinese civilization : the explication and exploration of Chinese characters - Huang, Dekuan (Sage, 2018)
The Key to Chinese Civilization: The Explication and Exploration of Chinese Characters is a fascinating guide to the history of the Chinese civilization, which has been recorded not just by means of the Chinese characters but also in the characters themselves. It studies the long history of Chinese characters, the laws of their construction and development, and what their correct interpretation can mean for contemporary communication. The Chinese writing system, vastly different from phonetic alphabet systems and the oldest continuously used system of writing in the world, is dynamic and its evolution reveals much about the historical and sociocultural development of China.